GAYA BERCERITA DEWI LESTARI DALAM TETRALOGI SUPERNOVA - Riska Wahyuni (Balai Bahasa Kalimantan Barat, 2018)
The research problem is about the story telling style of Dewi Lestari in Supernova tetralogy especially about the character and setting. The research purpose are to describe about the story telling style of Dewi Lestari concerning the characters and setting in Supernova tetralogy. The research is using descriptive method and qualitative form. Tetralogy Supernova consists of Kesatria, Putri, dan Bintang Jatuh; Akar; Petir; and Partikel. Based on the result of the research, story telling style of Dee related to Dee characters that uses various techniques to describe his characters. The techniques are expocitory, dialogue, behavior, thinking used and feeling, and reaction of other characters which used by Dee completely in Supernova tetralogi. The five techniques used by Dee are to show the personality of all characters. Consciousness flow technique is used by Dee in KPBJ and Petir novels. But this technique can not be found in Akar and Partikel novel. Character reaction technique is used in Akar and Petir novels. But this technique can not be found in KPBJ and Partikel novels. Physic and setting description technique is also used by Dee to show the characters personality in Akar, Petir, and Partikel. These two technique can not be found in KPBJ novel. The description character techniques used shows that Dee’s story telling style is more dominant using expository, dialogue, behaviour, thingking and feeling, and reaction of other characters because they can be found in four Supernova novels. The techniques used by Dee is to show the personality of the characters. The story telling style by Dee deals with setting that Dee uses several dominant settings in tetralogy Supernova. Place setting like foreign country and big city. Time setting like 20 century and 21 st century. Social setting like spiritual or religion, supernova letter, internet, free life, and friendship. Dee uses similar setting in every Supernova tetralogy. The similarity creates the uniqueness in Dee’s story telling style concering setting.